Pengaruh Pendidikan Orang Tua, Status Ekonomi dan Angka Putus Sekolah terhadap Keputusan Menikah Dini di Desa Pamatan Tongas Probolinggo - Diana Novita Sari; Sugeng Pradikto (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This research is motivated by the high rate of early marriage in Pamatan Village, which is a serious social issue and impacts the quality of life of the younger generation. This phenomenon is thought to be influenced by various social factors, including parental education level (X₁), family economic status (X₂), and school dropout rate (X₃). The purpose of this study is to analyze the influence of these three independent variables on the decision to marry early (Y). This study uses an explanatory quantitative approach with an ex post facto design, where the researcher does not intervene on the variables, but rather analyzes the relationships that have occurred. The analysis technique used is multiple linear regression. Data were collected through questionnaires to 100 respondents selected using a purposive sampling technique, namely teenagers or families with a history of early marriage. The results of the analysis show that simultaneously the variables of parental education, economic status, and school dropout rate have a significant influence on the decision to marry early with a calculated F value of 139.302 which is greater than the F table of 2.699 and a significance value of 0.001. Partially, only economic status (X₂) and school dropout rate (X₃) significantly influence the decision to marry early, while parental education (X₁) does not have a significant influence. The Adjusted R Square value of 0.807 indicates that 80.7% of the variation in the decision to marry early can be explained by these three variables. This finding underscores the importance of efforts to improve education and empower family economics as a preventive measure to reduce the rate of early marriage among adolescents in the village.